Comprehensive analysis of gene expression profiles reveals novel candidates of chemotherapy resistant factors in canine lymphoma. (October 2017) - Suenaga, Miyu; Tomiyasu, Hirotaka; Watanabe, Manabu; Ogawa, Kotogo; Motegi, Tomoki; Goto-Koshino, Yuko; Ohno, Koichi; Sugano, Sumio; Skorupski, Katherine A.; Tsujimoto, Hajime
Highlights: Changes in gene expression profiles at chemotherapy resistance were analyzed in dogs with lymphoma. Many dogs showed decreased expression of genes associated with immune responses and inflammatory reactions. Eleven genes were extracted as novel chemotherapy resistance factor candidates. Abstract: The molecular mechanisms of acquisition of chemotherapy resistance in canine lymphoma have not been elucidated. The aim of the present study was to identify novel molecular mechanisms of chemotherapy resistance by a comprehensive analysis of changes in gene expression profiles (GEPs). Tumor samples were obtained from 10 dogs with lymphoma at chemotherapy sensitive and chemotherapy resistant phases. During chemotherapy resistance, the expression of genes associated with immune responses and inflammatory reactions was decreased compared to chemotherapy sensitive phases. In addition, 11 genes, with significant changes in expression ( P  < 0.05), were extracted from seven dogs with chemotherapy resistant lymphoma. Further studies are needed to investigate the associations of these changes in GEPs with the acquisition of chemotherapy resistance in canine lymphoma.